A Phenomenological Study of Older Individuals' Experiences of Safety at Home - Kivimäki, Taina; Stolt, Minna; Charalambous, Andreas; Katajisto, Jouko; Suhonen, Riitta (Wiley, 2026)
Aims and objectives: To identify the elements of safety for older individuals living at home and how they describe safety as a lived experience.
Methodological design and justification: The research design was based on a phenomenological inquiry. The narratives were older individuals' own experiences of safety at home.
Ethical issues and approval: The study followed Finnish law and the European Code of Conduct for Research Integrity. The university committee of ethics gave ethical approval, and permission to conduct the study was granted from one wellbeing services county.
Research methods: Ricœur's Hermeneutic Phenomenological Analysis method was used to examine 16 older individuals' life experience of safety at home. The data was collected using a semi-structured interview framework and two structured instruments.
Results: Safety at home was expressed in many ways as being safe, living safely, and having a safe feeling with other people and most often in a positive manner. Older individuals' narratives of safety related to safe living in one's own home; being able to take care of oneself; reminiscing and longing; living at home is meaningful and valuable; changes in physical functioning; getting help from homecare and others.
Study limitations: The selection of participants was approached by homecare professionals and contact persons, who recruited older individuals to participate in the study. Whilst the inclusion criteria were known, the selection time was short, so not all potential participants were reached within this time.
Conclusions: For older individuals, safety at home means prerequisites for their daily life, including their unique perspectives and lived experiences. There is a need to explore diverse cultural contexts and employ longitudinal approaches to investigate how factors such as closeness to nature or social isolation contribute to older individuals' experiences of safety in their living environment.
Keywords: experiences; home; interview; older individuals; phenomenological; safety.